Analisis Likuiditas, Solvabilitas, dan Profitabilitas sebagai Indikator Kinerja Keuangan PT Indofood Sukses Makmur Tbk Periode 2019-2023 - M Juni Azka An-nur; Neni Rakhmawati (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study was conducted with the aim of evaluating the dynamics of the financial condition of PT Indofood Sukses Makmur Tbk over a five-year period, namely from 2019 to 2023. This writing applies a quantitative descriptive methodology sourced from secondary data through audited annual financial reports. The main instruments in this data analysis include three pillars of financial ratios: Current Ratio (CR) as a representation of the liquidity aspect, Debt to Asset Ratio (DAR) to measure the level of solvency, and Return on Equity (ROE) as a benchmark for the effectiveness of the company's profitability. Through annual calculations and trend analysis, this study captures the development of the issuer's performance longitudinally. The results of the observation show a significant strengthening in the company's liquidity position, where the Current Ratio jumped from 127% in 2019 to 192% at the end of the 2023 period. In line with that, the solvency profile shows fundamental improvements; Debt reliance, which had reached 51% in mid-2020-2021, was successfully reduced to 46% in 2023. Meanwhile, the company's profitability demonstrated stable resilience, with a consistent ROE of 10% to 13%, despite fluctuations due to operational cost dynamics. Overall, PT Indofood Sukses Makmur Tbk demonstrated excellent financial health through strategic capital and asset management. As a sustainability measure, management is advised to continue optimizing current assets and tightening cost efficiency to secure future profit margins.